Permodelan ekstraksi fluida superkritis - M Margono (ASOSIASI PENDIDIKAN TINGGI TEKNIK KIMIA INDONESIA (APTEKIM), 2004)
Supercritical Fluid Extraction have been used widely in the natural material industries, because it produced excellent mass transfer properties, ease solubility control due to temperature and pressure. A mathematical model based on shrinking-core model of the extraction process and simulation were used. Mechanism of the extraction process involves dissolution of solute, diffusion to the surface of a solid particle in the porous region (intraparticle diffusion), and mass transfer across stagnant film around the solid particle. Partial differential equation involves steady-state, axial convection and mass transfer from surface of the particle through a film around it were used to solve this model equation. The curves of Peclet number, Biot number on the extracted concentrations are compared to study the effects of operating conditions on concentration extracted of modeling. A developing model is the aim of this work where it could be used to get data and plot the whole curves, while the result of experiments could not work well. It is concluded that a